2012
DOI: 10.1111/bjdp.12001
|View full text |Cite
|
Sign up to set email alerts
|

Head and eye movements affect object processing in 4‐month‐old infants more than an artificial orientation cue

Abstract: This study investigates the effects of attention-guiding stimuli on 4-month-old infants' object processing. In the human head condition, infants saw a person turning her head and eye gaze towards or away from objects. When presented with the objects again, infants showed increased attention in terms of longer looking time measured by eye tracking and an increased Nc amplitude measured by event-related potentials (ERP) for the previously uncued objects versus the cued objects. This suggests that the uncued obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 75 publications
12
64
0
Order By: Relevance
“…Alpha desynchronization is a sensitive measure for attentional mechanisms that suppress irrelevant information and therefore focus attention on relevant information (Ward, 2003). Social cues such as eye gaze or head turn can guide infants' attention and can lead to enhanced memory encoding of cued objects in 4-month-olds (Hoehl, Wahl, et al, 2014;Hood, Willen, & Driver, 1998;Reid & Striano, 2005;Reid et al, 2004;Wahl et al, 2013). Thus, alpha desynchronization in the object-directed condition may reflect focused attention to gaze cued objects and thereby be related to social learning processes (Hoehl, Michel, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alpha desynchronization is a sensitive measure for attentional mechanisms that suppress irrelevant information and therefore focus attention on relevant information (Ward, 2003). Social cues such as eye gaze or head turn can guide infants' attention and can lead to enhanced memory encoding of cued objects in 4-month-olds (Hoehl, Wahl, et al, 2014;Hood, Willen, & Driver, 1998;Reid & Striano, 2005;Reid et al, 2004;Wahl et al, 2013). Thus, alpha desynchronization in the object-directed condition may reflect focused attention to gaze cued objects and thereby be related to social learning processes (Hoehl, Michel, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby it could enable or at least facilitate object learning in such situations. Similar processes might take place already at 4 months as infants differentiate between eye gazes toward and away from objects and build stronger memory representations for cued objects (Hoehl et al, 2008;Hoehl, Wahl, et al, 2014;Reid & Striano, 2005;Reid et al, 2004;Wahl et al, 2013). In the current study, eye gaze that is directed toward an object identifies it as an object that is of high relevance for the infant.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Using a live joint attention ERP paradigm adapted from Striano, Reid, and Hoehl [2006], Parise et al [2008] showed that even 5-month-olds' brain responses to objects are increased by a triadic interaction involving mutual gaze. When infants are presented short movies of adults turning either isolated eye gaze or combined head and gaze direction towards objects within the infants' immediate visual field, effects on object processing are even found in 4-month-old infants [Hoehl, Wahl, Michel, & Striano, 2012;Reid & Striano, 2005;Reid, Striano, Kaufman, & Johnson, 2004;Wahl, Michel, Pauen, & Hoehl, 2013]. Rather than speaking for abrupt changes in infants' joint attention capabilities, these results indicate continuity in infants' use of triadic interactions to focus their attention and facilitate object encoding throughout the first year of infancy.…”
Section: Triadic Interactions and Infants' Object Processing In The Fmentioning
confidence: 85%
“…Although these studies are suggestive of social learning from eye gaze and joint attention (see Reid & Dunn,Chap. 3,this volume) for an expanded discussion of this issue), they lack converging behavioral evidence confirming that the cortical response is functionally significant (for an exception, see Wahl, Michel, Pauen, & Hoehl, 2013).…”
Section: Contextual Modulation Of Faces and Objectsmentioning
confidence: 99%